Seasonal effects on the 10-deacetylbaccatin III and 19-hydroxybaccatin III contents of the needles of Taxus wallichiana Zucc. in Lam Dong province - Toan Phan, Nguyen Huu; Dieu Thuan, Nguyen Thi; Hao, Nguyen Cong; Minh, Chau Van (Academia Journal of Biology, 2014)
In Vietnam, there are two Taxus species (Taxus chinensis (Pilg.) Rehd. in Northern provinces and Taxus wallichiana Zucc. in Western Highland). Previous examinations show that content of taxoid compounds in the needles of T. chinensis is lower than in the needles of T. wallichiana, so that materials from T. chinensis don’t meet the requirements of pharmaceutical industry. Taxus wallichiana Zucc. (Taxaceae) only distributes in Lamdong province of Vietnam. Its needles were collected monthly from May 2005 to April 2006. The humidity of fresh needles was variety from 59 to 71 percent depending on seasonal conditions. Uniformly dried samples of Taxus wallichiana Zucc. were extracted and analyzed for their contents of two taxanes, namely 10-deacetylbaccatin III (DAB) and 19-hydroxybaccatin III (HB) using high pressure liquid chromatography instrument with the standard compounds. The content of DAB in the dried needles gradually increases according to the harvest time from January to July and sequentially decreases to the end of year. The maximum content of DAB is 0.037% in the dried needles collected in June or July. The lowest level was reached in February – March (0.012%). Similarity, the highest content of HB is 0.032% based on dried needles collected in June. The minimum level of HB is 0.014% on needles collected in January. Data obtained from a seasonal study showed that the best time to harvest of the yew clippings for the production of these two taxanes is approximately one month from the start of flushing (June to July). At that time the clippings have reached reasonable size to provide high quality biomass.